2019
DOI: 10.4103/ijpvm.ijpvm_197_17
|View full text |Cite
|
Sign up to set email alerts
|

Time series analysis of monthly suicide rates in West of Iran, 2006–2013

Abstract: Introduction: Iran's western provinces have higher suicide rate compared to the other provinces of the country. Although suicide rates fluctuate over time, suitable statistical models can describe their underlying stochastic dynamics. Methods: This study was conducted to explore the fluctuations of the monthly suicide rates in the most populated western province of Iran using exponential smoothing state space model to compute the forecasts. For this reason, the monthly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…However, the patterns we detected in 4 of 5 countries in this study are consistent with prior reports of seasonal patterns for circulatory system disease-related mortality [ 12 , 13 , 27 – 29 ] and for suicide in a number of countries and regions [ 10 , 11 , 24 , 25 , 30 42 ]. Although we cannot infer from our data whether cross-correlations exist in other countries, studies of temporal patterns of suicide or circulatory disease-related mortality in Canada, Chile, Finland, Greece, Hungary, Iran, Italy, Norway, and Sweden report apparently inverse temporal patterns for suicide [ 10 , 31 , 33 , 38 45 ] and for circulatory disease-related mortality [ 13 , 14 , 29 , 46 , 47 ]. Accordingly, it seems possible that the cross-correlations we identified in 4 countries also exist in other countries.…”
Section: Discussionmentioning
confidence: 64%
“…However, the patterns we detected in 4 of 5 countries in this study are consistent with prior reports of seasonal patterns for circulatory system disease-related mortality [ 12 , 13 , 27 – 29 ] and for suicide in a number of countries and regions [ 10 , 11 , 24 , 25 , 30 42 ]. Although we cannot infer from our data whether cross-correlations exist in other countries, studies of temporal patterns of suicide or circulatory disease-related mortality in Canada, Chile, Finland, Greece, Hungary, Iran, Italy, Norway, and Sweden report apparently inverse temporal patterns for suicide [ 10 , 31 , 33 , 38 45 ] and for circulatory disease-related mortality [ 13 , 14 , 29 , 46 , 47 ]. Accordingly, it seems possible that the cross-correlations we identified in 4 countries also exist in other countries.…”
Section: Discussionmentioning
confidence: 64%
“…In this study, county-level counts of suicide deaths in Kermanshah province were obtained from the dataset provided by the provincial Forensic Medicine Organization (FMO). Death certificates issued by the FMO have been accepted as a valid mortality data source for epidemiologic studies of suicide [4][5][6][7]10]. The corresponding populations of counties are obtained from the 2016 national census of population and housing [11].…”
Section: Data Collection and Data Analysismentioning
confidence: 99%
“…A previous study conducted in Kermanshah has also reported multiple individual level factors associated with the risk of attempted or completed suicide [6]. Determining the temporal and seasonal patterns of disease helps identify different spatial patterns over time and improve our understanding of the risk factors affecting the distribution of disease and death across the population and set them in the form of geographical maps [5,7]. Meanwhile, a previous ecological study has been conducted to visualize spatial heterogeneity in suicide mortality risk across the counties of the province [8].…”
Section: Introductionmentioning
confidence: 99%